2008
DOI: 10.1111/j.1365-2133.2008.08674.x
|View full text |Cite
|
Sign up to set email alerts
|

Perifolliculitis capitis abscedens et suffodiens successfully controlled with infliximab

Abstract: many cutaneous manifestations of systemic disease and the use of potentially toxic systemic therapies were felt to be the most important reasons for possessing this qualification.In 1993, following the General Medical Council's recommendations, 2 new undergraduate curricula were introduced in all U.K. medical schools. However, undergraduate exposure to dermatology at the time remained highly variable 1 and our findings suggest that this still appears to be the case. Over the past decade significant work has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…In addition, there are reports of successful treatment with doxycycline (10), ciprofioxacin (11), rifampicin {\2), dapsone (3), and adalimumab (13) as well as infiiximab (14). Berne et al (15) reported healing after zinc substitution therapy for at least 3 months.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, there are reports of successful treatment with doxycycline (10), ciprofioxacin (11), rifampicin {\2), dapsone (3), and adalimumab (13) as well as infiiximab (14). Berne et al (15) reported healing after zinc substitution therapy for at least 3 months.…”
Section: Discussionmentioning
confidence: 96%
“…Some case series have noted successful treatment with TNF‐α inhibitors such as infliximab and adalimumab, 7,8 but post‐treatment biopsies note residual sinus tracts and disease activity returning within 4 weeks of discontinuation of treatment 8 . Other approaches include radiation‐induced epilation, carbon dioxide and pulsed diode lasers, and incision and drainage 9–12 .…”
Section: Discussionmentioning
confidence: 99%
“…Because the pathogenetically related hidradenitis suppurativa has been shown to respond favorably to tumor necrosis factor (TNF) targeted therapy, 5,6 we decided to treat DCS with the monoclonal anti-TNF antibody adalimumab. Moreover, we were encouraged by a recent single case report 7 of successful treatment of DCS with the monoclonal anti-TNF antibody infliximab. At the same time, we questioned the sustainability of such an exclusively anti-inflammatory monotherapy in view of the underlying structural disease of DSC.…”
mentioning
confidence: 99%